Assembly of Neuronal Connectivity by Neurotrophic Factors and Leucine-Rich Repeat Proteins - Ledda, Fernanda; Paratcha, Gustavo (Frontiers in Cellular Neuroscience, 2016)
Proper function of the nervous system critically relies on sophisticated neuronal networks interconnected in a highly specific pattern. The architecture of these connections arises from sequential developmental steps such as axonal growth and guidance, dendrite development, target determination, synapse formation and plasticity. Leucine-rich repeat (LRR) transmembrane proteins have been involved in cell-type specific signaling pathways that underlie these developmental processes. The members of this superfamily of proteins execute their functions acting as trans-synaptic cell adhesion molecules involved in target specificity and synapse formation or working in cis as cell-intrinsic modulators of neurotrophic factor receptor trafficking and signaling. In this review, we will focus on novel physiological mechanisms through which LRR proteins regulate neurotrophic factor receptor signaling, highlighting the importance of these modulatory events for proper axonal extension and guidance, tissue innervation and dendrite morphogenesis. Additionally, we discuss few examples linking this set of LRR proteins to neurodevelopmental and psychiatric disorders.